"Constructing a health assessment questionnaire for people with intellectual disabilities: A cognitive interview study". Issue 3 (10th October 2019) - Bakker‐van Gijssel, Esther J.; Lucassen, Peter L. B. J.; olde Hartman, Tim C.; Assendelft, Willem J. J.; van Schrojenstein Lantman‐de Valk, Henny M. J.
Abstract: Introduction: Health assessment instruments can help to raise awareness among general practitioners of specific health problems in people with intellectual disabilities (PID). The present authors developed a health assessment questionnaire using the cognitive interview technique (CI) to improve the comprehensibility. The utility of this approach to questionnaire development involving PID is assessed. Method: A qualitative approach using the CI was employed. The study included PID and their caregivers. The present authors interviewed 14 participants in 5 subsequent rounds. After each round, the questionnaire was adjusted until saturation was reached. Results: Three hundred and sixty three identified problems led to 316 changes to the questionnaire. Most problems (102) concerned the comprehension of the question, followed by problems in the "missing answer categories" and "inaccurate instruction" section. Conclusion: The comprehensible health assessment questionnaire can help PID to take an active role in communication with their GP. The use of CI helped to improve the questionnaire. CI is a usable and valuable procedure for PID.